The Effect of lifestyle Modification According To physical - Counseling Program On Some Functional Indicators In Patients With Diabetes - Saleh, Hamid; Khalil, Nabeel (Journal of Physical Education, 2019)
The research aimed at modifying unhealthy lifestyle with healthy style in individuals with type 2 diabetes through applying physical – counseling program. In addition to that it aimed at identifying the effect of physiological indicators like blood pressure level and body mass index. The researchers used the experimental method on (10) male diabetic individuals. The program was applied for 12 weeks with 36 training sessions three sessions per week. The results showed significant statistical differences between pre and posttests. The researchers concluded that physical – counseling program have positive effect on lowering blood pressure. Finally they recommended modifying life style to lower blood pressure and body mass index.